What Makes Forensic Psychiatric Experts Change Their Opinion in Supplemental Evaluations? - Periša, Ante (International journal of offender therapy and comparative criminology, 2023)
There are cases in forensic psychiatric evaluations with inconclusive information or with important information missing. In such situations, when new information becomes available the judge may ask an expert to supplement his/her report in the light of new information. For the purpose of this study, we collected 42 supplemental evaluations written in the University Psychiatric Hospital Vrapče to determine possible factors which were associated with changes in supplemental evaluations. The following data were gathered: demographic data, types of criminal offenses, reasons for the supplement evaluation, court questions, and diagnoses. Changes in supplemental evaluations occured more often when the defendants were diagnosed with a personality disorder (PD) only, compared to those who had a PD with a comorbidity, especially substance use disorders. Defendants with the diagnosis of a substance use disorder were 63.7% less likely to have changed experts’ evaluations. The evaluations remained the same when the reason for supplemental evaluations were new witnesses’ testimonies. Considering the principle of economy of actions in a judiciary system, a more critical approach should be taken when the judge requests a supplemental report.